Moral Degradation in Ahmad Tohari’s Novel Ronggeng Dukuh Paruk - ., Hidayati; Nasution, Siti Norma; Lubis, Masdiana (KnE Social Sciences, 2019)
The research is actuated by phenomenon of deterioration in the character of a person or group of community members who are generally influenced by the development of the times and advances of technology, imbalanced with the moral consciousness termed moral degradation. Moral degradation is a social problem that can have a negative impact on individuals, community groups, and the state. The purpose of this study is to reveal the existence of moral degradation in Ahmad Tohari’s novel Ronggeng Dukuh Paruk using a qualitative descriptive method, precisely selected as the object of research is related to social phenomena, namely symptoms or events that occur and can be observed in social life. The research is imperative to do as when morality of an individual or group of community members cannot be maintained as already shifted from a noble cultural, moral degradation arises which furthermore if uncontrolled can cause greater social problems. The data in this study are written data derived from phrases and sentences indicating the existence of moral degradation carried out by characters in the novel. Data collection is done by referring to the note-taking method. The results show that there are two points of moral degradation in this novel: human trafficking and hypocrisy. Keywords: moral degradation, human trafficking, hypocrisy